(3eHGOF aj GdgfOSI GdeOfjI ddCbSGe GdcgQHjI hGdejcGfjcjI hGdcjeGFjIs - (3YHjOh, EHQGgje Ydjs; (3GdYOhj, eMeO UGObs ((3HjQhJ (B:s (3OGQ GdQGJH GdLGeYjI,s, 1987)
(3JCKjQ NhGU GdJQHI Ydi GdebGheI GdcgQHjI(B.s
Keywords: (3GdgfOSI GdeOfjIs; (3GdgfOSI GdejcGfjcjIs; (3GdgfOSI GdcjejGFjIs; (3GdgfOSI GdcgQHGFjIs